Observations of Slow Solar Wind from Equatorial Coronal Holes - Wang, Y.-M.; Ko, Y.-K. (The Astrophysical journal, 2019)
Because of its distinctive compositional properties and variability, low-speed ( 450 km s−1) solar wind is widely believed to originate from coronal streamers, unlike high-speed wind, which comes from coronal holes. An alternative scenario is that the bulk of the slow wind (excluding that in the immediate vicinity of the heliospheric current sheet) originates from rapidly diverging flux tubes rooted inside small coronal holes or just within the boundaries of large holes. This viewpoint is based largely on photospheric field extrapolations, which are subject to considerable uncertainties and do not include dynamical effects, making it difficult to be certain whether a source is located just inside or outside a hole boundary, or whether a high-latitude hole will be connected to Earth. To minimize the dependence on field-line extrapolations, we have searched for cases where equatorial coronal holes at central meridian are followed by low-speed streams at Earth. We describe 14 examples from the period 2014-2017, involving Fe xiv 21.1 nm coronal holes located near active regions and having equatorial widths of ∼3°-10°. The associated in situ wind was characterized by speeds v ∼ 300-450 km s−1 and by O7+/O6+ ratios of ∼0.05-0.15, with v showing the usual correlation with proton temperature. In addition, consistent with other recent studies, this slow wind had remarkably high Alfvénicity, similar to that in high-speed streams. We conclude that small coronal holes are a major contributor to the slow solar wind during the maximum and early post-maximum phases of the solar cycle.